2016
DOI: 10.1016/j.diabres.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Do worms protect against the metabolic syndrome? A systematic review and meta-analysis

Abstract: This review has shown that helminth infections can be associated with improved metabolic outcomes. Understanding of the mechanisms underlying this relationship could facilitate the development of novel strategies to prevent or delay T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 37 publications
3
59
0
1
Order By: Relevance
“…It may therefore be reasonable to employ a regimen where cohorts of children are screened and treated as part of health screening procedures as they reach adulthood. Furthermore, as noted above, there is increasing evidence that pre-existing helminth infections may have beneficial effects on metabolic parameters in later life, and this potential effect may need to be taken into consideration when considering treatment in populations where type 2 diabetes mellitus is extremely prevalent [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be reasonable to employ a regimen where cohorts of children are screened and treated as part of health screening procedures as they reach adulthood. Furthermore, as noted above, there is increasing evidence that pre-existing helminth infections may have beneficial effects on metabolic parameters in later life, and this potential effect may need to be taken into consideration when considering treatment in populations where type 2 diabetes mellitus is extremely prevalent [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of papers concerning helminth infection and metabolic syndrome found that individuals with a previous or current helminth were 50% less likely to have an endpoint metabolic dysfunction comparted to uninfected individuals [37]. In addition, there is evidence that the human intestinal microbiomes (here including parasitic worms) influence who develops allergy, atopy and autoimmune disease and who does not.…”
Section: Essential Learning Objectivesmentioning
confidence: 99%
“…In contrast, the prevalence of inflammatory metabolic diseases, such as Type 2 diabetes mellitus (T2DM) is high in high-income countries. The absence of exposure to helminth infections has been postulated as one mechanism to explain this markedly increased prevalence of T2DM [2][3][4][5][6]. Recent observational studies in India, Indonesia, China and Australia have reported that the prevalence of helminth infections was significantly lower in T2DM individuals compared to non-diabetic controls [4,5,7,8], thus confirming a protective effect of helminths against T2DM pathogenesis.…”
Section: Introductionmentioning
confidence: 98%